PENGARUH BRAND IMAGE DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN DI RESTORAN KEDAI KITA BOGOR - Sofiani, Sofiani; Tatiana Putri Yulia, (Journal of Innovation Research and Knowledge, 2024)
Culinary tourism is related to the activity of visiting a place, the aim of which is to carry out culinary tourism. Brand Image has many aspects that can influence a company, therefore companies can try to present a good Brand Image with the products that consumers have in mind. Companies that have a positive impact can also increase a good Brand Image and vice versa, if they have a bad Brand Image this can be detrimental to the company. Price is one of the factors that most influences a purchasing decision. Kedai Kita Bogor, which was founded in 2008, sells wood-fired pizza and hot plate noodles. Wood-fired pizza is the most popular because it is cooked specifically, namely grilled with firewood, resulting in a pizza with a different taste compared to pizza found in other places. The purpose of this research is to find out whether Brand Image and Price influence purchasing decisions at the Kedai Kita Bogor Restaurant. The method that will be used is quantitative using a questionnaire method so that the research gets results that are right on target. It can be concluded from all the test results that brand image and price have quite a large influence at 47.8%. This is based on the brand image of our shop in Bogor which is already very good because it has quality food that uses imported ingredients, but in terms of price Our shop does have a fairly high price range so this has quite a big influence on consumers' purchasing decisions